Critical Layer Thickness Analysis of Vertically Stacked Hyperbolic Metamaterials for Effective Negative Refraction Generation. Issue 11 (16th September 2020) - Cho, Hanlyun; So, Sunae; Badloe, Trevon; Bang, Sanghun; Rho, Junsuk
Abstract: Vertically stacked narrow metal‐dielectric multilayered structures known as vertical hyperbolic metamaterials (vertical HMMs) are proposed for broadband negative refraction. The thickness of each layer is required to be subwavelength for effective medium theory (EMT) to be applicable. Therefore, each layer should be thin, forcing the aspect ratio to become extremely high. This requirement makes the fabrication of vertical HMMs difficult. Thus, it is important to determine the limit of the layer thickness for the realization of vertical HMM. In this study, the critical layer thicknesses of vertical HMMs are investigated numerically at the wavelengths of 400, 500, 600, and 700 nm. It is concluded that the critical layer thicknesses for both vertical and horizontal HMMs depend on the permittivity along the perpendicular direction of the layers. The maximum critical layer thickness of vertical HMMs, with a value of 0.22, is produced by a structure composed of gold and silicon dioxide at the wavelength of 500 nm, while the critical layer thickness tends to be smaller if silver is employed. It is believed that this study can provide a useful database as quantitative indicators which can be exploited in designing nanostructures using EMT. Abstract : Negative refraction is observed using vertically stacked hyperbolic metamaterials (vertical HMMs). Critical layer thicknesses of HMMs for clear negative refraction are numerically investigated. Critical layer thicknesses of both vertical and horizontal HMMs are determined by the permittivity along the perpendicular direction of the HMMs. The size and properties along the nanostructure's characteristic direction are dominant to apply effective medium theory.